Kewajiban Indonesia Menurut International Covenant On Civil And Political Rights Atas Kekerasan Terhadap Kelompok Transgender - Ilman Ramadhanu; Siti Muslimah (Faculty of Law Universitas Sebelas Maret, 2018)
This study aimed to understand the obligations of Indonesia according to International Covenant on Civil and Political Rights regarding violence acts toward transgender community in Indonesia. This study uses the normative method with conceptual and statute approach. Legal materials are collected through library study and analyzed through deductive method. The study shows that as a member of ICCPR, Indonesia has yet to fully perform its obligation to respect, protect, and fulfill transgender rights especially regarding violence. In respecting transgender rights, Indonesia allows change of sex, however there are still problematic regulations that are often used to justify violence towards transgender. Regulations that are meant to preventively protect transgender do not have any provisions that prohibits gender-based violence and law enforcement seems absent in punishing the perpetrators. Remedial measure has been provided with complaint mechanism through Indonesia’s National Human Rights Commission.The fulfillment of transgender rights have been shown by adding transgender issues as one of priorities of Indonesia’s National Human Rights Commission.